Fermentasi biji durian khas Kalimantan sebagai pengganti tepung terigu dengan metode perendaman berseri - Jefri Pandu Hidayat; Siti Munfarida; Asful Hariyadi (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Durian seed modification is aimed at increasing the functional properties of a wheat flour alternative. The research combined immersion in Na2S2O5 and fermentation using L. plantarum solution. The influence among the solid consistency, starter concentration, and time process variable by Complete Randomized Design (RAL) duplicate experiment to get superlative condition. Runge-Kutta (RK) third-order method used the kinetic modeling algorithm. The RK solver was completed using the optimization solver in Ms. Excel 2021. The analysis of variance (ANOVA) was performed using Minitab 18.1. The functional properties parameters were measured consisting of carbonyl, carboxyl, degree of substitution, swelling power, solubility, water and oil absorption. The maximum specific growth rate of L. plantarum was 1.902/hours and the brown pigment degradation rate was 0.0016/minutes. It showed that the best form for time preliminary process was 120 minutes. It is followed by a raw material consistency of 15% (w/v), a starter concentration of 5% (v/v) at 24-hour fermentation. At the best process condition, the modified durian seed flour have carboxyl content 1.028%, carbonyl 0.48%, degree of substitution 0.078, swelling power 8.5 g/g, water solubility 7.64%, water and oil absorption capacity, 162.43% and 28.81% respectively. Whereas the functional properties are still not close to commercial wheat flour SNI 3751:2018. Hereafter, the parametric using growth model was expressed for the future bio-reactor design.